2019
DOI: 10.1039/c9nr07643c
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/alginate composites as novel bioinks for three-dimensional mesenchymal stem cell printing and bone regeneration applications

Abstract: Three-dimensional (3D) cell printing is a versatile technique enabling the creation of 3D constructs containing hydrogel and cells in the desired shape or pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 51 publications
1
130
0
Order By: Relevance
“…In 3D printed scaffolds specifically, in addition to the structural and physicochemical properties of the composite materials, geometrical features such as pore size, pore area, and strand diameter play important roles 50,60 . While most studies have reported that incorporating the GFMs into scaffolds and structures improves their mechanical performance 51,[61][62][63][64][65] , a few studies have shown differing results in which the addition of rGO has had no effect or adverse effects on the mechanical performance of the constructs 35,66 . The variations in between studies and the mechanical enhancements observed in our 3D printed constructs, is likely due to variations in all the above-mentioned parameters as well as the differing geometrical features.…”
Section: Mechanical Evaluation Of the 3d Printed Scaffoldsmentioning
confidence: 99%
“…In 3D printed scaffolds specifically, in addition to the structural and physicochemical properties of the composite materials, geometrical features such as pore size, pore area, and strand diameter play important roles 50,60 . While most studies have reported that incorporating the GFMs into scaffolds and structures improves their mechanical performance 51,[61][62][63][64][65] , a few studies have shown differing results in which the addition of rGO has had no effect or adverse effects on the mechanical performance of the constructs 35,66 . The variations in between studies and the mechanical enhancements observed in our 3D printed constructs, is likely due to variations in all the above-mentioned parameters as well as the differing geometrical features.…”
Section: Mechanical Evaluation Of the 3d Printed Scaffoldsmentioning
confidence: 99%
“…rGO-alginate hydrogels protect mesenchymal stem cells thanks to reactive oxygen species scavenging (Choe et al, 2019a). GO-alginate is bioprintable and bioconductive effects have been observed in many tissue engineering applications, paving the way for skeletal muscle reconstruction studies (Choe et al, 2019b).…”
Section: Graphene Compositesmentioning
confidence: 99%
“…Lee and co-workers reported an alginate bioink formulation prepared with a 3% wt/vol alginate concentration, which could be used to print 3D MSCs scaffolds. 65 The addition of graphene oxide (0.05-1.0 mg mL À1 ) significantly enhanced the capability of the cells to undergo osteogenic differentiation, probably due to increased mechanical stiffness of the gels. The authors tried to explain this osteoinductive behaviour, by suggesting that the graphene oxide could help to support the scaffold integrity and provide mechanical cues to MSCs for osteogenesis.…”
Section: Mesenchymal Stem Cells Bone and Cartilage Scaffoldsmentioning
confidence: 99%
“…Alginate bioinks can also be used for the 3D printing of mesenchymal stem cells that can then differentiate into different lines forming (for example) cartilage 70 or bone scaffolds. 65,66,69 In most of the reported examples, these hard tissue scaffolds were obtained using an alginate concentration between 2.0-3.0% wt/vol in combination with other additives such as graphene oxide, hydroxyapatite or growth factors. The preparation of polysaccharide blends using agarose, cellulose, methylcellulose, gellan gum and hyaluronic acid can also be a successful strategy to improve the mechanical properties of the resulting 3D printed structures and their stability and integrity over time (Fig.…”
Section: Design Of Alginate-based Bioink Formulations For Specific Apmentioning
confidence: 99%